Kiat Meningkatkan Daya Tahan Tubuh dan Pembiasaan Cuci Tangan di SDN Candirejo 02 - Kurnia Choerunisa; Dita Arisca Devi; Ossa Alifiyanti Kulsum; Lalu Helmi Maulana; Richa Yuswantina; Niken Dyahariesti; Dwi Retna Susilowati (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
This research is motivated by the low understanding of SDN Candirejo 02 students regarding the importance of immune system and proper handwashing, which potentially increases the risk of infectious diseases. This research aims to enhance children's understanding and awareness of the importance of maintaining personal hygiene and health through a Community Service program. This community service activity was conducted by the Pharmacy Professional Students of Ngudi Waluyo University at SDN Candirejo 02, using counseling methods, handwashing demonstration and simulation, and question and answer sessions, with the goal of improving the knowledge of 4th-grade students about the importance of maintaining immune system and proper handwashing. An evaluation of 25 students using pre-test and post-test methods showed that before the counseling, demonstration, and handwashing simulation, 64% of students had an understanding of handwashing habits. After the presentation of the material, there was a 28% increase, leading to an improvement in student understanding. The activities were conducted through counseling methods, handwashing simulation, and question and answer sessions. Despite the increase in understanding, there were still misunderstandings regarding the importance of handwashing after handling money. It is hoped that activities like this can be regularly conducted to enhance awareness of personal hygiene. Recommendations are made to enhance education on hand hygiene, especially after handling money, both in the school and family environments to ensure that clean and healthy living habits are firmly ingrained in students. Regular counseling is highly recommended to support this.   ABSTRAK Latar belakang penelitian ini dilandasi oleh masih rendahnya pemahaman siswa SDN Candirejo 02 tentang pentingnya daya tahan tubuh dan cuci tangan yang benar, sehingga berpotensi meningkatkan risiko penyakit infeksi. Penelitian ini bertujuan untuk meningkatkan pemahaman dan kesadaran anak-anak tentang pentingnya menjaga kebersihan diri dan kesehatan melalui program pengabdian Masyarakat. Kegiatan pengabdian masyarakat ini dilakukan oleh Mahasiswa Profesi Apoteker Universitas Ngudi Waluyo di SDN Candirejo 02, menggunakan metode penyuluhan, demonstrasi dan simulasi cuci tangan serta sesi tanya jawab, dengan tujuan meningkatkan pengetahuan siswa kelas 4 tentang pentingnya menjaga daya tahan tubuh dan mencuci tangan dengan benar.  Evaluasi terhadap 25 siswa dengan metode pre-test dan post-test menunjukkan bahwa sebelum kegiatan penyuluhan, demonstrasi, dan simulasi cuci tangan, 64% siswa telah memahami kebiasaan mencuci tangan. Setelah pemaparan materi, terjadi peningkatan sebesar 28%, sehingga pemahaman siswa meningkat. Kegiatan dilakukan dengan metode penyuluhan, simulasi cuci tangan, dan sesi tanya jawab. Meskipun terjadi peningkatan pemahaman, masih terdapat kesalahpahaman terkait pentingnya mencuci tangan setelah memegang uang. Diharapkan kegiatan seperti ini dapat rutin dilakukan untuk meningkatkan kesadaran akan kebersihan diri. Saran, edukasi tentang kebersihan tangan, terutama setelah memegang uang, perlu ditingkatkan secara berkelanjutan di sekolah dan rumah agar kebiasaan hidup bersih dan sehat tertanam kuat pada siswa.  Penyuluhan rutin sangat dianjurkan untuk mendukung hal ini.